2022
DOI: 10.1088/1361-651x/ac11ba
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale constitutive model for metal forming of dual phase titanium alloys by incorporating inherent deformation and failure mechanisms

Abstract: Ductile metals undergo a considerable amount of plastic deformation before failure. Void nucleation, growth and coalescence is the mechanism of failure in such metals. α–β titanium alloys are ductile in nature and are widely used for their unique set of properties such as specific strength, fracture toughness, corrosion resistance and resistance to fatigue failures. Voids in these alloys have been reported to nucleate on the phase boundaries between α and β phase. Based on the findings of crystal plasticity fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(279 reference statements)
0
2
0
Order By: Relevance
“…In more sophisticated modeling efforts, the finer details of the α − β colony are explicitly incorporated into the CPFE models. Prior works that utilized this approach have analyzed the effects of salient microstructural characteristics of the lamellar grains, such as β-phase volume fraction, lamellae thickness, the relative orientation of the primary slip direction in the α phase, the number of prior β grains, and the number of α colonies per grain, on the effective ductility, yield strength, strain-rate sensitivity, resistance to dwell fatigue, strain localization, formability and resilience to void growth and coalescence [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In more sophisticated modeling efforts, the finer details of the α − β colony are explicitly incorporated into the CPFE models. Prior works that utilized this approach have analyzed the effects of salient microstructural characteristics of the lamellar grains, such as β-phase volume fraction, lamellae thickness, the relative orientation of the primary slip direction in the α phase, the number of prior β grains, and the number of α colonies per grain, on the effective ductility, yield strength, strain-rate sensitivity, resistance to dwell fatigue, strain localization, formability and resilience to void growth and coalescence [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers found that the α phase microstructure with a scale gradient obtained during heat treatment was conducive to improving the comprehensive matching of the strength and toughness of titanium alloys [19,20]. For titanium alloys, the multiscale lamella structure exhibits an improved strength-fracture toughness combination that is better than that of the single lamella structure and bimodal structure, which is mainly attributed to the more tortuous crack propagation path caused by the multiscale lamella microstructure [21].…”
Section: Introductionmentioning
confidence: 99%